2017
DOI: 10.1002/hbm.23735
|View full text |Cite
|
Sign up to set email alerts
|

Neural signature of inattentional deafness

Abstract: Inattentional deafness is the failure to hear otherwise audible sounds (usually alarms) that may occur under high workload conditions. One potential cause for its occurrence could be an attentional bottleneck that occurs when task demands are high, resulting in lack of resources for processing of additional tasks. In this fMRI experiment, we explore the brain regions active during the occurrence of inattentional deafness using a difficult perceptual-motor task in which the participants fly through a simulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 58 publications
(88 reference statements)
11
28
0
Order By: Relevance
“…For instance, experiments conducted in flight simulators, reveal that perfectly audible critical warning alarms could fail to reach awareness (Dehais, Tessier, Christophe, & Reuzeau, ; Dehais et al, , ). In these contexts, the visual modality is thought to suppress hearing via the implementation of gating mechanisms at the visuo‐auditory integrative stage (Lebib, Papo, de Bode, & Baudonnière, ; Molloy et al, ) via direct visuo‐auditory connections or through higher level attentional systems (Durantin, Dehais, Gonthier, Terzibas, & Callan, ).…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…For instance, experiments conducted in flight simulators, reveal that perfectly audible critical warning alarms could fail to reach awareness (Dehais, Tessier, Christophe, & Reuzeau, ; Dehais et al, , ). In these contexts, the visual modality is thought to suppress hearing via the implementation of gating mechanisms at the visuo‐auditory integrative stage (Lebib, Papo, de Bode, & Baudonnière, ; Molloy et al, ) via direct visuo‐auditory connections or through higher level attentional systems (Durantin, Dehais, Gonthier, Terzibas, & Callan, ).…”
Section: Introductionmentioning
confidence: 73%
“…Within the context of inattentional deafness, which is the lack of awareness of an auditory alarm, it is maintained that under high load conditions or those requiring focused attention to the primary task, that attentional modulation of secondary tasks is attenuated or perhaps even the networks involved with the secondary tasks are selectively inhibited (Durantin et al, ). This is consistent with decreased N1 ERP amplitude found under high workload conditions in response to auditory stimuli (Molloy et al, ; Scannella et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent analysis of alerting systems' role in aviation accidents, Mumaw (2017) found that pilots quite often failed to detect or even understand incoming visual or auditory alerts (see also Bliss, 2003). Poorly designed alarms are particularly worrisome in that they can greatly increase stress or distract pilots (Peryer et al, 2005;Doll et al, 1983) thereby failing to establish sufficient awareness-an effect that is especially prominent during flight phases that put severe demands on the pilots (Durantin et al, 2017). In contrast, correct and trustworthy alarms can reduce not only pilots' cognitive load but also establish an appropriate picture of the situation and hence enhance their performance.…”
Section: Blunting the Impact Of The Warning Effectmentioning
confidence: 99%